The Use of Theater and Drama Techniques to Foster Speaking Skills in the English Class - SalaS alvarado, Jonnathan (Revista de Lenguas Modernas, 2017)
The use of theater techniques can go beyond the stage. The following article aims to demonstrate this assertion. The article presents eight activities based on theater games that were adapted taking into consideration the contents and objectives of the English national syllabus established by the Minister of Public Education of Costa Rica. Each activity is described in detail to provide the reader with an easy guide for their application. At the same time, the author provides information that claims for the effectiveness of the use of theater techniques in teaching- learning processes. El uso de las técnicas teatrales puede ir más allá del escenario y este estudio tiene el objetivo de demostrar esta aserción. El artículo presenta ocho actividades basadas en juegos teatrales que fueron adaptadas tomando en cuenta contenidos y objetivos del programa nacional de inglés establecido por el Ministerio de Educación Pública de Costa Rica. Cada actividad está descrita detalladamente para dar al lector una guía fácil para su aplicación. Al mismo tiempo, el autor brinda información que asegura la efectividad del uso de las técnicas teatrales en los procesos de enseñanza y aprendizaje.